New possibilities of pharmacotherapy for systemic lupus erythematosus: Prospects for the use of anifrolumab (monoclonal antibodies to type I interferon receptor) - E. L. Nasonov; A. S. Avdeeva; T. V. Popkova (Научно-практическая ревматология, 2021)
Systemic lupus erythematosus (SLE) is a systemic autoimmune rheumatic disease of unknown etiology, characterized by overproduction of organ-specific autoantibodies to various components of the cell nucleus and the development of immune-inflammatory damage to internal organs. According to modern concepts, one of the key mechanisms of SLE immunopathogenesis is associated with dysregulation of type I interferon (IFN) synthesis The complex of data obtained in the process of fundamental and clinical research served as the basis for the development of a new approach to the pharmacotherapy of SLE, associated with the use of monoclonal antibodies (mAbs) that block the activity of IFN type I or its receptors. Among these drugs, anifrolumab (AFM) occupies a special place, which is a human IgG1 mAbs that bind to cellular receptors for IFN-α. The article discusses the materials of the main studies concerning the efficacy and safety of AFM in SLE, and the prospects for the use of this drug in the treatment of this disease.